2020
DOI: 10.1177/2057158520946212
|View full text |Cite
|
Sign up to set email alerts
|

Competency requirements for the assessment of patients with mental illness in somatic emergency care: A modified Delphi study from the nurses’ perspective

Abstract: Patients suffering from mental illness are vulnerable, and they do not always have access to proper emergency care. The aim of this study was to identify competency requirements for the assessment of patients with mental illness by soliciting the views of emergency care nurses. A modified Delphi method comprising four rounds was used. Data were collected in Sweden between October 2018 and March 2019. The data were analyzed using content analysis and descriptive statistics. The panel of experts reached the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
(59 reference statements)
0
9
0
3
Order By: Relevance
“…Andersson et al . (2020) also found that nurses believe that effective communication skills are important when providing care to individuals with MIH. Horgan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Andersson et al . (2020) also found that nurses believe that effective communication skills are important when providing care to individuals with MIH. Horgan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Despite such reproductions, there are attempts by professionals to achieve the best possible care within the existing conditions, and to establish effective communication with both the user and his family. Theoretical and practical knowledge, communication skills, and a respectful attitude toward the patient are essential competence requirements for assessing people with mental disorders (29) . Satisfactory levels of knowledge promote increased confidence, positive attitudes, empathy and improvement in the quality of care provided (5,30) seem to be the way to a care based on ethical and legal precepts and the realization of the rights of this public in health services, especially in emergency rooms.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously confirmed that to ensure appropriate patient assessment, different nurses must meet the competency requirements for assessing patients with mental illness [ 20 ]. These competency-related demands often include situation awareness, history gathering, communication, and procedural skills [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that patient assessments are adequate and appropriate, ambulance nurses’ mental health competencies must correspond with the requirements of their profession. Earlier results identified three key areas of competency for assessing patients with mental illness in emergency care: adequate theoretical and practical knowledge, extended communication skills, and a respectful attitude [ 20 ]. This result is in line with Edmund et al, who concluded that education and training, organizational factors, and clinical decision-making are important in ambulance care to ensure an appropriate response to the needs of people experiencing mental health issues [ 8 ].…”
Section: Discussionmentioning
confidence: 99%